Undergraduate Students' Attitudes Toward and Perceptions of Hospitality Careers in Mainland China. Issue 3 (3rd July 2019) - Wen, Han; Li, Xiaoye; Kwon, Junehee
ABSTRACT: This study aimed to identify and evaluate factors that influence Chinese hospitality students' career decision-making processes based on a modified perception importance analysis approach. A total of 614 usable responses were collected from 16 hospitality programs in China through an online survey. Results showed that compensation, benefits, and promotion opportunities in the hospitality industry were below students' expectations and in need of improvement. In addition, industry–person congeniality (β = 0.319, p < .001), social factors (β = 0.182, p < .001), and career development opportunities (β = 0.183, p < .001) were identified as the significant factors influencing students' career decision-making processes (F = 81.509, R2 = 0.446). To improve recruitment and retention of future employees in the hospitality industry, managers should concentrate their efforts to improve critical job-related attributes identified in this study. Hospitality educators are advised to improve their curricula to better prepare students for hospitality careers.